A family of related Co(II) terpyridine compounds exhibiting field induced single-molecule magnet properties. (15th March 2018) - Higgins, Robert F.; Livesay, Brooke N.; Ozumerzifon, Tarik J.; Joyce, Justin P.; Rappé, Anthony K.; Shores, Matthew P.
Graphical abstract: Syntheses, crystal structures and magnetic properties for three Co(II)-tpy complexes are presented. All three Co compounds display field-induced slow relaxation of magnetization. We find that coordination geometry affects the dynamics of this relaxation, which is supported by computational studies. Abstract: We describe the syntheses, crystal structures and magnetic properties of several Co(II) complexes containing 4′-pyrrolidine-2, 2′:6′, 2″-terpyridine (pyrtpy) or 4′-triflouromethylsulfonate-2, 2′:6′, 2″-terpyridine (OTftpy) ligands: [(OTftpy)CoCl2 ] (1 ), [Co(pyrtpy)2 ](BPh4 )2 (2b ), and [(OTftpy)Co(κ2 -O2 NO)2 ] (3 ). The compounds display different coordination numbers, where 1, 2b and 3 are distorted square pyramidal (pentacoordinate), octahedral (hexacoordinate) and pentagonal bipyramidal (heptacoordinate) about the cobalt center, respectively. Field-induced slow magnetic relaxation properties are observed for all compounds; however, compounds 1 and 3 display two relaxation events, whereas 2b shows only one relaxation event. The origin of the varied dynamic magnetic properties for these complexes arises from the change in coordination environment as well as dipolar interactions between neighboring complexes. These experimental results are supported by computational investigations for each species, implicating lower-lying excited states for complex 2b, which increase the impact of spin–orbit coupling, in turn leading to a larger axial anisotropy value.